Proses Pengungkapan Diri Perokok Wanita Berjilbab di Lingkungan Pertemanan Bukan Perokok - Renindyana Putri, Afrida; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The process of self-disclosure of a hijabi as a smoker is complex to reveal or hide the identity of her smoker. The smoker's identity is considered to conflict with her religious identity, namely the symbol of the hijab she wears. Researchers conducted this study intending to know the process of self-disclosure of hijabi smokers in their non-smoker friends. This study uses a qualitative research method, which refers to the interpretive paradigm with a phenomenological approach. The theory used in this research is the theory of Communication Privacy Management (CPM) by Sandra Petronio. The data collection technique used in this research is an in-depth interview with the research subject, namely the hijabi smoker. The study results revealed that the process of self-disclosure of hijabi as smokers to their non-smoker friends begins with self-identification. Accept personal characteristics and life goals to behave according to the needs and expectations of society. Environmental factors and self-awareness influence identification. Then the second stage is to reveal oneself to the environment. Hijabi smokers experience the tension of rejection and have several criteria for consideration. Consideration of the interlocutor's culture, contextual considerations, consideration of the magnitude of risks and benefits, and motivation for disclosure. Selfdisclosure requires trust and intimacy and is done directly (consciously), indirectly (unconsciously), and through social media. The hijabi women smokers feel happy when accepted by their environment. When experiencing conflict, a hijabi smoker will explain her background, experiences, and thoughts—intended so that the interlocutor can understand and produce acceptance. However, if they still experience rejection, hijabi smokers choose to ignore it. Hijabi smokers maintain relationships with their non-smoker friends by accepting their identity, expressing themselves openly, and showing their achievements and good ethics. There are hijabi smokers who deny their identity by hiding one of their identities to avoid conflict. Not all veiled female smokers have a good religious background, some wear the hijab because of fashion, and parental demands.